SARS-CoV-2 B.1.1.7 UK Variant of Concern Lineage-Related Perceptions, COVID-19 Vaccine Acceptance and Travel Worry Among Healthcare Workers - Temsah, Mohamad-Hani; Barry, Mazin; Aljamaan, Fadi; Alhuzaimi, Abdullah N.; Al-Eyadhy, Ayman; Saddik, Basema; Alsohime, Fahad; Alhaboob, Ali; Alhasan, Khalid; Alaraj, Ali; Halwani, Rabih; Jamal, Amr; et al. (Frontiers in Public Health, 2021)
Background: Healthcare workers’ (HCWs’) travel-related anxiety needs to be assessed in light of the emergence of SARS-CoV-2 mutations. Methods: An online, cross-sectional questionnaire among HCWs between December 21, 2020 to January 7, 2021. The outcome variables were HCWs’ knowledge and awareness of the SARS-CoV-2 B.1.1.7 lineage that was recently reported as the UK variant of concern, and its associated travel worry and Generalized Anxiety Disorder (GAD-7) score. Results: A total of 1,058 HCWs completed the survey; 66.5% were female, 59.0% were nurses. 9.0% indicated they had been previously diagnosed with COVID-19. Regarding the B.1.1.7 lineage, almost all (97.3%) were aware of its emergence, 73.8% were aware that it is more infectious, 78.0% thought it causes more severe disease, and only 50.0% knew that current COVID-19 vaccines are effective in preventing it. Despite this, 66.7% of HCWs were not registered to receive the vaccine. HCWs’ most common source of information about the new variant was social media platforms (67.0%), and this subgroup was significantly more worried about traveling. Nurses were more worried than physicians (P=0.001). Conclusions: Most HCWs were aware of the emergence of the SARS-CoV-2 B.1.1.7 variant and expressed substantial travel worries. Increased worry levels were found among HCWs who used social media as their main source of information, those with lower levels of COVID-19 vaccine uptake, and those with higher GAD-7 scores. The utilization of official social media platforms could improve accurate information dissemination among HCWs regarding the Pandemic’s evolving mutations. Targeted vaccine campaigns are warranted to assure HCWs about the efficacy of COVID-19 vaccines toward SARS-CoV-2 variants.